Hydrological and flood hazard assessment using a coupled modelling approach for a mountainous catchment in Portugal - Fonseca, A. R. (2019)
Floods may lead to destruction of property, to damage to the environment and ultimately to loss of lives. Although it is not possible to avoid them, they are enhanced by human activities that increase the probability of occurrence of these natural events. Preliminary flood risk assessment and determination of areas of potential significant flood risk is mandatory according to the European Floods Directive (2007). In order to meet the established legislation, a methodology was developed that couples two modelling approaches: the Hydrological Simulation Program—FORTRAN (HSPF) and IBER. A target watershed, with complex orography and known to be vulnerable to flood hazards, is selected: the Vez River (northern Portugal). The performance of the HSPF model, driven by a climate gridded dataset, was assessed, followed by the reconstruction of the flow rate in the catchment for the period from 1950 to 2015. The results hint at an agreement between simulated and observed daily flow rates, with high coefficient of determination value and of the Nash–Sutcliffe coefficient of efficiency ([0.7 daily timescale). A satisfactory performance was also found in reproducing flood peak events. An average deviation of 10% was found between observed and simulated flood peaks. The output of HSPF was subsequently used to drive IBER, thus determining flood hazard areas for a 10, 50 and 100-year return periods. The methodology presented here provides basic tools for decision-makers to evaluate hydrologic responses to climate data, namely the determination of flood hazard maps, but also risk assessment, water management, environmental protection and sustainability.